2012
DOI: 10.1080/15472450.2012.691842
|View full text |Cite
|
Sign up to set email alerts
|

Driver Behavior and Preferences for Changeable Message Signs and Variable Speed Limits in Reduced Visibility Conditions

Abstract: This article investigates the factors affecting drivers' stated behavior in adverse visibility conditions and examines whether drivers rely on and follow advisory or warning messages displayed on portable changeable message signs (CMS) and/or variable speed limit (VSL) signs in different visibility and traffic conditions, and on two types of roadways: freeways and two-lane roads. A multiple-approach survey was designed to collect opinions and stated data from Central Florida drivers.Categorical data analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Existing literature (not related to work zone, but to other road sections) shows mixed results on influence of gender on speed choice. Mannering (2007) found that males drive faster than females according to self-report data, while females are reported to be more cautious (Hassan et al, 2012) and more supportive of lower speed limits (Debnath et al, 2013;Lahausse et al, 2010). Male drivers were also found to be less likely to believe that their safety is threatened when driving 10 mph (16.1 km/h) over posted speed limit (Mannering, 2009).…”
Section: Effects Of Driver Characteristics On Self-nominated Speedsmentioning
confidence: 99%
“…Existing literature (not related to work zone, but to other road sections) shows mixed results on influence of gender on speed choice. Mannering (2007) found that males drive faster than females according to self-report data, while females are reported to be more cautious (Hassan et al, 2012) and more supportive of lower speed limits (Debnath et al, 2013;Lahausse et al, 2010). Male drivers were also found to be less likely to believe that their safety is threatened when driving 10 mph (16.1 km/h) over posted speed limit (Mannering, 2009).…”
Section: Effects Of Driver Characteristics On Self-nominated Speedsmentioning
confidence: 99%
“…Erke et al (2007) found that the information supplied by Variable Message Sign (VMS) has a very effective role in changing driving routes. Hassan et al (2012) declared that the content of the information has a great influence on drivers' safety perception. Otherwise, the location where to release the information also plays an important role in drivers' behavior (Jiang, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lots of models and methods were used to analyze the impact factors how to influence drivers, including the Bayesian learning model (Kobayashi, 1994), the multinomial logit model (Wardman et al, 1997), the binary contingent choice model (Anderson, et al, 2006), bivariate and multivariate probit models (Hassan et al, 2012) and the structure equation model (Fujii et al, 2009). The analysis of variance method was applied to study the drivers' response to vehicle induction information (Adler, 2001).…”
Section: Technical Notementioning
confidence: 99%
“…Driver obedience for the speed guidance value affected the effect directly. The effect might also lose even play a negative role when the traffic demand reached a certain level [34][35][36][37]. Models of these researches were established under accident data, so it requires a lot of high-quality traffic accident data.…”
Section: Problem Backgroundmentioning
confidence: 99%